Aplicação do geoprocessamento na elaboração e revisão de planos diretores na região imediata de Belém – PA - BARROS, Ester Naiana Rodrigues (2022)
The master plan is a mandatory document for municipalities with more than twenty thousand inhabitants that is essential for urban planning, in accordance with the provisions of the Federal Constitution of 1988 and the statute of the city. From that, the present study aimed to analyze the application of geoprocessing in the preparation and review of master plans in the Immediate region (IR) of Belém, state of Pará, Brazil, highlighting that IR are groups of municipalities that have as main references the urban network and have a local urban center as a basis, through the analysis of IBGE. The following study began with a bibliographic survey on the problem and cartographic documentary survey. Specifically, a more detailed analysis was made for 4 (four) municipalities, of small or medium population size all of them in the interior of the state and outside the Metropolitan Region of Belém (MRB):Acará, Barcarena, Bujaru e Concórdia do Pará. Only in one the municipality (IR) has no master plan, and in another the plan, although elaborated, is in the process of being approved by the legislature. However, the lack of updating of plans in most municipalities allows understanding the technical difficulties- associated with political factors- for the fulfillment of municipal and urban planning by municipal governments, within the period established by law (10 years). It was noted for the case studies, the technical and professional deficiency that permeates the use of geoprocessing by the teams involved in the preparation and review of the master plans, both in the diagnosis and in the annexes of the approval laws, which includes the preparation of the maps. The study concluded from the reality in analysis the need for training of professionals in the area working in public planning and management.